General Practitioners' Experiences During the First Phase of the COVID-19 Pandemic in Italy: A Critical Incident Technique Study - Kurotschka, Peter Konstantin; Serafini, Alice; Demontis, Michela; Serafini, Arianna; Mereu, Alessandro; Moro, Maria Francesca; Carta, Mauro Giovanni; Ghirotto, Luca (Frontiers in Public Health, 2021)
Since February 2020, when coronavirus disease (COVID-19) began to spread in Italy, creating one of the biggest disease clusters worldwide, general practitioners (GPs) were called to manage a growing number of health situations while reorganizing their care provision. The challenges experienced by Italian GPs remained unrevealed. A qualitative study design involving the critical incident technique through an online survey was applied. Sociodemographic data and open-ended responses were collected. While participants’ characteristics were analyzed through descriptive statistics, the framework method was used to explore the qualitative data. 149 GPs from all over the country responded to the survey. Most respondents (66.4%) were aged ≤35 years, 38.9% were male, and 26 declared that they were or had been quarantined. 99 participants completed the survey (dropout rate = 33%). The framework analysis resulted in six themes: (1) organization and infrastructure of the healthcare services, (2) impact of COVID-19 on Italian general practice, (3) management of COVID-19, (4) doctor–patient relationship, (5) professional collaboration, and (6) GPs’ emotions and reflections. Participants reported problems regarding coordination and communication between the different services involved in the emergency response. Critical incidents included huge obstacles in communicating with other local services, and a lack of authoritative guidance was reported as a major challenge. Although the respondents felt positively about the digital technologies adopted for remote patient consultations, the pandemic revealed critical issues regarding the organization of primary care in Italy and its relationship with the rest of the healthcare system. Many GPs were overwhelmed by the intensity of the COVID-19-related activities. The GP–patient relationship emerged as a positive element and many responses addressed the importance of teamwork during the pandemic, in terms of both professional and emotional support. This study suggests that GPs in Italy are not part of any coherent strategy that prepares the Italian primary care service for epidemic outbreaks. Communication and coordination between primary care and public health authorities are essential and should be substantially improved, and publicly funded institutional general practice research should be initiated to collect the context-specific evidence necessary to enhance the system’s preparedness regarding public health emergencies.